PENGARUH TAMBAHAN PENGHASILAN PEGAWAI (TPP) TERHADAP KINERJA PEGAWAI BPKAD KAB. DOMPU - Siti Fatimah Tussyauri; Irwansyah Irwansyah; Hermansyah Hermansyah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2025)
This study aims to determine the effect of Employee Income Supplement (TPP) on the performance of BPKAD employees of Dompu Regency. The method used in this study is quantitative descriptive. The Sample Technique uses a saturated sample of 52 employees or the entire population is used as a sample. The data collection technique used a questionnaire with a likert scale. Data analysis used Simple Linear Regression, determination coefficient test and t test with the help of SPSS version 24. Based on the results of the study, it is shown that the free variable (X), namely additional employee income, has a positive and significant influence on the bound variable (Y), namely Performance. This is shown through a simple linear regression equation, namely: Y = 18.937 + 0.502X. The correlation value (r) is 0.627 in a positive direction. The coefficient value of the determination (r2/R Square) is 0.394 or 39.4%. The variation in performance of 39.4% can be explained by the variation in the provision of additional employee income. The value of the t-test (significance test) is 5.697 with a significance of 0.000 < 0.05, meaning that the Additional Employee Income (TPP) has a significant influence on the performance of BPKAD employees of Dompu Regency